2005
DOI: 10.1007/s00240-005-0487-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of luminal oxalate or calcium oxalate on renal tubular cells in culture

Abstract: Oxalate or calcium oxalate crystal-induced tissue damage could be conducive to renal stone disease. We studied the response of renal proximal (LLC-PK1 and MDCK-II) and collecting (RCCD1 and MDCK-I) tubule cell lines to oxalate ions as well as to calcium oxalate monohydrate (COM) crystals. Cells grown on tissue culture plastic or permeable growth substrates were exposed to high (1 mM) and extremely high (5 and 10 mM) oxalate concentrations, or to a relatively large quantity of crystals (146 microg), after which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Some papers (Kim, Kwak, Jeong, & Kim, ; Werness, Brown, Smith, & Finlayson, ) have reported that high concentrations of oxalate (1 mM) led to cell apoptosis in MDCK cells; however, Verkoelen, Schepers, van Ballegooijen, and Bangma () reported that cell apoptosis can be induced by extremely high oxalate concentration (5 and 10 mM) but not by high oxalate concentration. Borges et al () and Verkoelen et al () have confirmed this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Some papers (Kim, Kwak, Jeong, & Kim, ; Werness, Brown, Smith, & Finlayson, ) have reported that high concentrations of oxalate (1 mM) led to cell apoptosis in MDCK cells; however, Verkoelen, Schepers, van Ballegooijen, and Bangma () reported that cell apoptosis can be induced by extremely high oxalate concentration (5 and 10 mM) but not by high oxalate concentration. Borges et al () and Verkoelen et al () have confirmed this finding.…”
Section: Discussionmentioning
confidence: 99%
“…A high concentration of oxalate contributes to COM precipitation. Oxalate and/or COM induce cellular oxidative stress in the kidneys with increasing free radical production, which creates a harmful environment for macromolecules and results in cell damage and even apoptosis or cell death 912 . Moreover, different types crystals generate different amounts of ROS, but to be sure, they all show toxicity to cells 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Both are known to have cytotoxic effects on cultured renal cells 45–48. However, although earlier investigations showed that oxalate is cytotoxic at concentrations as low as 250 µ M (reviewed in 45), more recent studies have reported it to be innocuous up to 5 m M 47–50, which is the highest urinary oxalate concentration to have been documented in the hyperoxaluric rat model of nephrolithiasis 18. Furthermore, one of those studies 48 showed that oxalate cytotoxicity resulted specifically from the formation of COM crystals.…”
Section: Discussionmentioning
confidence: 99%